The right to a compulsory share in inheritance: comparative legal aspect - Babiuk, Petro (Actual problems of law (Aktual’ni problemi pravoznavstva), 2021)
The European integration vector of Ukraine’s development as a state and its legislation highlights the need for comparative legal research on the legal regulation of inheritance relations in Ukraine and other European countries. Along with the principle of freedom of testament, the law provides for the limits of such freedom, primarily to protect the interests of testatorʼs family members and close relatives. In the legislation of European countries, there are two systems for this - the reserve and the compulsory share. In some countries (France, Switzerland, Spain, Italy) the law provides for the division of inherited property into two parts – reserved (mandatory) and disposable. Thus, the testator may, by making a testament, dispose in case of death only of the disposable part of the inheritance. The reserve system restricts the testator’s freedom in such a way that in the testament he can dispose of only that part of the inheritance («free share») which exceeds that reserved for the obligatory heirs. In other countries, such as Germany, Austria, the Netherlands, and Poland, a certain category of persons is entitled to a compulsory share. That is, the inheritance passes to the heirs appointed in the testament, but the persons to whom it belongs are entitled to a compulsory share, have the right to demand from these heirs to pay them their compulsory share. Ukraine and other post-Soviet countries of Europe are characterized by a system of compulsory share, although it differs from it’s «classical» model. If there are obligatory heirs and they accept the inheritance, the latter will inherit the part of the inherited property that corresponds to the size of their compulsory share. Although a testator is free to define the scope of inheritance and to appoint of heirs in the testament, but after his death, the distribution of inheritance will be based on persons entitled on the obligatory share.